West African Female Sex Workers in Mali: Reduction in HIV Prevalence and Differences in Risk Profiles of Sex Workers of Differing Nationalities of Origin. (1st March 2015) - Trout, Clinton H.; Dembélé, Ouman; Diakité, Daouda; Bougoudogo, Flabou; Doumbia, Bakary; Mathieu, Jacques; Haidara, Amadou; Sangaré, Adama; Traoré, Sékou; Burtner, Joanna; Cabral, Howard; Messersmith, Lisa J.
Abstract : Background: Female sex workers (FSW) in Mali are highly vulnerable to HIV. Their prevalence in 2009 was 9 times higher (24.2%) than that among pregnant women (2.7%). Methods: Four Integrated HIV/sexually transmitted infection (STI) Surveillance and Behavioral Surveys among FSW in Mali (2000, 2003, 2006, and 2009) tracked demographic characteristics, behavior, and HIV and STI prevalence. Logistic regression using generalized estimating equations to control for the cluster effect identified factors associated with HIV-positive serostatus adjusting for potential confounding. Results: Of 2430 FSW, 40.8% were Nigerian, 36.8% were Malian, and 22.4% were from other neighboring countries. Between 2003 and 2009, HIV prevalence dropped from 44.14% to 28.49% ( P < 0.0001) among Malians, from 21.33% to 12.71% ( P = 0.0082) among Nigerians, and from 43.42% to 33.67% ( P = 0.0442) among "others." Between 2000 and 2009, condom availability increased (89.18%–99.3%; P < 0.0001) as did HIV testing (40%–75%; P < 0.0001). Consistent condom use with clients improved for Malians (72.3%–81.5%; P = 0.0092), but not among Nigerians (92.7%–90.94%; P = 0.8240) and "others" (88.9%–88.48%; P = 0.8452). Consistent condom use with boyfriends was low and improved only for Nigerians (9.8%–28.4%; P = 0.0003). Factors associated with HIV prevalence in the multivariate model were older age, study year (2003 and 2006), nationality, lack of education, mobility, STI symptoms, gonorrhea prevalence, and younger age at first sex. Conclusions: This study documents progress in the fight against HIV among FSW in Mali. The different vulnerabilities to HIV found for different nationality FSW should be considered in programming and future research.